'Leaders, ' 'followers' and collective group support in learning 'art music' in an amateur composer-oriented Bach Choir. Issue 3 (November 2014) - Einarsdottir, Sigrun Lilja
<x content-type="archive" xml:space="preserve">Abstract</x> The purpose of this paper is to demonstrate how amateur choral singers experience collective group support as a method of learning 'art music' choral work. Findings are derived from a grounded-theory based, socio-musical case study of an amateur 'art music' Bach Choir, in the process of rehearsing and performing the Mass in B Minor by J.S. Bach. Data collection consisted of participant observation, qualitative interviews and a paper-based survey. Findings indicate that in the process of learning a challenging choral work, participants use peer-learning as support and form supportive groups within each voice part, with 'informal leaders' supporting others ('followers') who are performing the work for the first time. On the other hand, performing a challenging work can also seem 'intimidating' for those less experienced singers. Findings also indicate that whereas followers (and the conductor) benefit from this group support, 'leaders' may experience a certain lack of musical challenge.